Protective effect of low dose caffeine on psychological stress and cognitive function - AKAKIN, DİLEK; ÖZBEYLİ, DİLEK; YÜKSEL, MERAL; KASIMAY ÇAKIR, ÖZGÜR (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Introduction: Caffeine is an adrenergic antagonist that enhances neuronal activity. Psychological stress depresses cognitive function. Aim: To investigate the effects of acute and chronic low dose caffeine on anxiety-like behavior and cognitive functions of acute or chronic psychological stressed rats. Material-method: Acute or chronic caffeine (3 mg/kg) was administered to male Sprague Dawley rats (200-250 g, n = 42) before acute (cat odor) and chronic variable psychological stress (restraint overcrowding stress, elevated plus maze, cat odor, forced swimming) induction. Anxiety and cognitive functions were evaluated byhole-board and object recognition tests. The brain glutathione and malondialdehyde assays, myeloperoxidase, nitric oxide (NO), superoxide dismutase (SOD), luminol and lucigenin activity and histological examination were done. ANOVA and Student's t-test were used for statistical analysis. Results: The depressed cognitive function with chronic stress exposure and the increased anxiety-like behavior with both stress inductions were improved via both caffeine applications (p < 0.05-0.001). Both caffeine pretreatments in chronic stressed rats, and chronic caffeine in acute stressed ones reduced the elevated myeloperoxidase activities (p < 0.05-0.01). The increased malondialdehyde, lucigenin and NO levels with acute stress were inhibited with chronic caffeine (p < 0.05-0.01), malondialdehyde and NO levels were declined by acute caffeine (p < 0.001). Acute caffeine decreased SOD activity (p < 0.01) and improved glutathione (p < 0.01) and luminol levels (p < 0.05). The induced histological damage with both stress exposures was ameliorated with chronic caffeine. Conclusion: The increased anxiety-like behavior and depleted cognitive functions under stress conditions were improved with both acute and predominantly chronic caffeine pretreatments by decreasing oxidative damage parameters. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Working memory; Oxidative damage; Acute stress; Chronic stress; Anxiety; NITRIC-OXIDE PRODUCTION; ACUTE RESTRAINT STRESS; OXIDATIVE STRESS; INDUCED ANXIETY; RATS; INFLAMMATION; ANTIOXIDANT; ADENOSINE; SYSTEM; DAMAGE